THE POLITICAL IMPLICATIONS OF ALASDAIR MACINTYRE’S CLAIMS OF DEPENDENT RATIONAL ANIMALS - Bielskis, Andrius (Problemos, 2012)
This paper engages with the key philosophical claims of Alalsdair MacIntyre’s Dependent Rational Animals. I argue that despite MacIntyre’s convincing accounts of an alternative Aristotelian social ontology, and the political structures of the common, his emphasis on the politics of communal self-defense is dubious unless the proponents of Aristotelian politics are in the position to challenge the power of limitless capital accumulation. The paper also engages with Aristotle’s conception of virtue and the role legislation plays in our attempts to acquire virtues. Finally, on the basis of Karl Marx’s distinction between necessary labour time and surplus labour time, this paper offers a new concept – Exploitation Calculus – which is designed to measure the level of the exploitation of labour in a given company.Keywords: Alasdair MacIntyre, Dependent Rational Animals, the politics of the common good, Aristotle, virtue, communal self-defense, emancipation, global capitalism, exploitation calculus.Alasdairo Macintyre’o veikalo „Priklausomi racionalūs gyvūnai“ teiginių politinės implikacijosAndrius BielskisSantraukaStraipsnyje analizuojami svarbiausi Alasdairo MacIntyre’o veikalo Priklausomi racionalūs gyvūnai teiginiai. Jame teigiama, kad, nepaisant MacIntyre’o pateikiamos įtikinamos alternatyvios aristoteliškos socialinės ontologijos ir bendrojo gėrio politinių struktūrų sampratos, jo akcentuojama bendruomenių protekcionistinė politika yra abejotina, jei aristoteliškos politikos šalininkai neturi galimybės pasipriešinti besaikei kapitalo kaupimo galiai. Straipsnyje taip pat yra aptariama Aristotelio dorybės samprata, o sykiu įstatymų leidybos reikšmė ugdant dorybes. Remiantis Karlo Marxo skirtimi tarp būtinojo ir pridedamojo darbo laiko, straipsnyje pateikiama eksploatacijos skaičiuoklės formulė.Pagrindiniai žodžiai: Alasdairas MacIntyre’as, Priklausomi racionalūs gyvūnai, bendrojo gėrio politika, Aristotelis, dorybė, emancipacija, globalus kapitalizmas, eksploatacijos skaičiuoklė.